"Save Romania" Union and the Persistent Populism in Romania. Issue 4 (4th July 2021) - Dragoman, Dragoș
ABSTRACT: The electoral success of the "Save Romania" Union (USR) in the 2016 parliamentary elections sheds new light on the rising populist parties in Romania and offers a new perspective on the Romanian political environment, showing how a new party succeeded in adapting to widespread populist expectations. USR managed to emerge as an important player by reviving old populist themes but in a more radical manner. The party continues to emphasize an anti-elitist orientation combined with a strong anti-corruption campaign, adopting a flamboyant political style based on permanent confrontation, verbal attacks, and extensive accusations.